Nutritional and dietary aspects in polycystic ovary syndrome: insights into the biology of nutritional interventions. (1st December 2020) - Neves, Luísa Pinheiro Pimenta; Marcondes, Rodrigo Rodrigues; Maffazioli, Giovana De Nardo; Simões, Ricardo Santos; Maciel, Gustavo Arantes Rosa; Soares, Jose Maria; Baracat, Edmund Chada
Abstract: Polycystic Ovary Syndrome (PCOS) is a complex endocrine disorder, which affects 5–17% of reproductive age women and is often associated with obesity and metabolic impairment. Common treatment strategies are based on exercise, diet and nutrient supplementation since PCOS is often linked with obesity and metabolic impairment. Studies have recommended that nutrition is a key factor in the health maintenance of women with PCOS, however, little is known about the subject in the context of such a disease. This narrative review aims to identify dietary and nutritional aspects of PCOS and discuss the role of nutrients in management of polycystic ovary syndrome in view of clinical trials.